Surfactin suppresses postharvest gray mold in Actinidia arguta fruit via direct antifungal activity and induced host resistance - Feiyang Wang; Sen Dong; Hang Che; Baodong Wei; Dazhi Zhang; Bingxue Li; He Gao; Shunchang Cheng (Food Control, 2027)

A probabilistic pedotransfer function for estimating the soil water characteristic curve and quantifying its uncertainty - Xin-Yuan Wang; He-Fu Pu; Ming Min; Yu Miao; Sen-Lin Xie; Xiao He (Computers and Geotechnics, 2027)

Biocontrol potential of Bacillus velezensis lut-Y1: Antifungal lipopeptides against postharvest fungi Alternaria alternata and Penicillium expansum - Hui-Jun Yuan; Yan-Sen Li; Wen-Jin Ma; Tian-Kun Zhao; Zhen-Dong Wang; Miao-Miao He; Shi-Man Yu; Yan-Ying Xu (Physiological and Molecular Plant Pathology, 2026)

Insights from stratigraphic reconfiguration induced by the South Pole-Aitken massive impact - Sheng Gou; Zongyu Yue; Yangting Lin; Bin Su; Zhanchuan Cai; Roberto Bugiolacchi; Kaichang Di; Patrick C. Pinet; Yuyang He; Honglei Lin; Hengci Tian; Sen Hu; et al. (Icarus, 2026)

Full-scale test and numerical study on seismic performance of double-sided superimposed shear walls with vertical UHPC slits in nuclear power plants - Kun Wang; Xiaoye Bai; Sen Yang; Wenfu He; Tao Wang (Engineering Structures, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Aerogel-based photothermal materials for environmental remediation and solar energy utilization: Materials chemistry, mechanisms, structural design, and applications - Tong Jing; Meng Dai; Fangying Hong; Huijun Yu; Sen Wang; Liang Guo; Tianguang Lu; Shuguang Wang; Zuoli He (Journal of Environmental Chemical Engineering, 2026)

City scale prediction of ground collapse dynamics and risks using hybrid simulation and deep learning methods - Yuchen Jia; Qinglun He; Wenfeng Bai; Yizhao Wang; Xiang Yang; Sen He; Junxia WuShan; Fei Wang (Engineering Geology, 2026)

Piezoelectric catalysis “nets-breaking and source-rescuing”: targeting and degrading neutrophil extracellular traps restores arginine metabolism for enhanced antitumor immunotherapy - Chang Liu; Sen Tan; Weili Xue; Wenkang Tu; Hengrui Liu; Meng Yuan; Yuchu He; Xuwu Zhang; Dawei Gao (Chemical Engineering Journal, 2026)

The EjWRKY22-Ej4CL5 module promotes loquat fruit browning by regulating lignin biosynthesis - Xin Jiang; Wenjuan Huang; Sen Chang; Hao Yang; Qianming Zheng; Xi Yan; Danlong Jing; Yan Xia; Suqiong Xiang; Qigao Guo; Qiao He; Shuming Wang (Postharvest Biology and Technology, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Combined suppression of Aspergillus parasiticus and aflatoxin B1 in marinades: unraveling the cooperative antifungal mechanism of linalool and surfactin - Qiqi Sun; Zhanrui Huang; Wanying He; Lianhua Hu; Yuebo Li; Xiaohu Zhou; Hao Chen; Sen Tao (Food Research International, 2026)

Bovine milk fat globule membrane-derived antioxidant peptides: Enzymatic optimization, peptidomic profiling, and cytoprotective evaluation - He Li; Dongrui Feng; Sen Wei; Xiaoyao Deng; Huixun Dong; Aihua Zhu; Shaobo Zhou (Food Bioscience, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Arbuscular mycorrhizal symbiosis decouples arsenic risk from saponin biosynthesis in Panax notoginseng (Araliaceae) by reprogramming rhizosphere and root processes - Xing-Kai Zhang; Xian-Nv Long; Shu-Shuang Tang; Tai-Xiong Zheng; Di Chen; Fu-Gang Wei; Yan-Lin Wang; Yue Wu; Kai Dai; Guan-Hua Cao; Sen He (Journal of Hazardous Materials, 2026)

Metabolomic and Ionomic analysis of the effects of different cultivation modes on the quality of Tieguanyin tea - Sen Wang; Liangquan Wu; Yiru Zhao; Zhengjia He; Zhiyi Liu; Wei Li; Lei Wu; Aosheng Jiang; He Chang; Hao Wu; Anni Wei; Jinlong Liu; et al. (Food Chemistry, 2026)

Intelligent and accurate recognition method of lining cracks under complex seam interference and engineering application - Xiaohua Xu; Yuanhai Li; Weiguo He; Shuo Yang; Chengbing Wang; Sen Wang (Tunnelling and Underground Space Technology, 2026)

MOF-derived hierarchically ordered Cu/C-ZnO nanosheets for high-performance triethylamine sensing - Wei Wei; Shuyi Ma; Wangwang Liu; Nina Ma; Ping Ni; Yinyue Wang; Heng Wang; Jiamin Zhu; Haiyan Wang; Runlin Liu; Rui He; Sen Zhang; et al. (Journal of Environmental Chemical Engineering, 2026)

Assessing the maintenance and renewal of genetic diversity in Cunninghamia lanceolata breeding populations through core collection construction - Sen Cao; Jingyong Ji; Bin Shen; Guowei Hu; Yin Liu; Guiping He; Zhichun Zhou; Zhen Zhang (European Journal of Forest Research, 2026)

Ejecta from Chaffee S Crater in Chang’E-6 Landing Site Constrained by Seifertite-Bearing Norite - Zhan Zhou; Sen Hu; Yubing Gao; Linxi Li; Huicun He; Liang Gao; Mengfan Qiu; Lixin Gu; Xu Tang; Xiaoguang Li; Wei Yang; Yangting Lin; et al. (Journal of Earth Science, 2026)

Klotho Attenuates Glucocorticoid-Induced Osteoblast Cytotoxicity Via Wnt Signaling Pathway Modulation - Sen Wang; Miao He; Xiao Liang; Baoshan Li (Biochemical Genetics, 2026)

Experimental Verifications and Applications of Discontinuous Deformation Analysis in Block-Type Rock Slope Failure and Movement Mechanisms - Guoyang Liu; Shouyi Luo; Sen Zhang; Ke Ma; Wu Bo; He Fan; Zewen Dong (Rock Mechanics and Rock Engineering, 2026)

Mitigation of sulfide stress on eelgrass Zostera marina and Manila clam Ruditapes philippinarum through an eelgrass–clam coculture system - Hang Zhang; Ziyi Xu; Sen Su; Qinxia Yang; Qiyin Tan; Yanlin Wang; Qinyi He; Xuefeng Chen; Weidong Gu; Changzi Ge (Ocean & Coastal Management, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

A laminated 3D desalinator with 3D energy trapping effect for high-efficient solar steam generation and desalination - Sen Ai; Zhi-Han Zhou; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Jun-Shuai Li; Xiang-Hu Gao (Process Safety and Environmental Protection, 2026)

Dynamics and drivers of last-resort antibiotic resistance genes during pilot-scale aerobic fermentation of municipal sludge and subsequent bok choy pot trials - Li-Tao Zhou; Da-Hai He; Jiang Li; Ruo-Xue He; Shi-Jin Ma; Guang-Yu Gong; Xiao-Shuang Zou; Sen Li; You-Fei Zhou; Wei-Jie Hu (Journal of Hazardous Materials, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

4-hydroxybenzoic acid-assisted formic acid preserves lignin structure during efficient hemicellulose removal in bamboo biorefinery - Weidong Li; Hanwen Ge; Sen Ma; Lei Liu; Lin Luo; Zihao Qin; Aiyong He; Chao Wang; Xianhai Zeng (Chemical Engineering Journal, 2026)

Amino-functionalized MOF separators enabling anion-confined and Li+-selective transport for ultra-stable and high-rate lithium metal batteries - Zhendong Hao; Wenjie Li; Guanyu Liu; Sen Qi; Yingfei Tang; Yuhong Jin; Li Wang; Chengjie Lu; Weifeng Huang; Shihai Cao; Xiangming He (Chemical Engineering Journal, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Effects of calcium chloride addition on the soot formation characteristics of ethylene pyrolysis in a laminar flow reactor - Qingyan He; Sen Shao; Qifeng Guo; Xiaoqing You (Journal of Aerosol Science, 2026)

Synergistic mechanism of hydrophobic and hydrophilic antioxidants in the interface of tree peony seed oil bilayer emulsion - Wen-Sen He; Na Wei; Jingyu Li; Qingzhi Wang; Haonan Yang; Chen Tan; Shouhe Huang; Huafang Ding; Jianhua Zhu; Hanyu Zhu; Zhen-Yu Chen (Food Chemistry, 2026)

THU-Wildfire: A multitemporal, multimodal observation dataset for wildfire behavior dynamics - Jiahao Zhou; Sen He; Shanjunxia Wu; Jia Zhang; Qiuhua Wang; Fei Wang (Environmental Modelling & Software, 2026)

Effect of Saturation State on Mudstone Mechanical Properties and the Fracture Zone Formation Around Mudstone Roadways - Jinghua Li; Guichen Li; Yuantian Sun; Fengzhen He; Haoran Hao; Sen Yang; Wei Li; Zhongwei Chen (Rock Mechanics and Rock Engineering, 2026)

Co-pyrolysis-to-co-gasification continuum of Pennisetum hydridum and waste tires: Temperature/atmosphere/synergy characterization of tar/char/gas products - Sen Lin; Xin Chen; Guopeng Ke; Jingyong Liu; Zhibin Chen; Leyao Tao; Weijie Li; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Yao He; Liangzhong Li (Journal of Cleaner Production, 2026)

Microbiota-driven shaping of volatile compound profiles in whole-plant corn silage: Impacts of Lactiplantibacillus plantarum, Lactiplantibacillus buchneri, and their co-inoculation during fermentation - Shuyuan Xue; Lunaike Zhao; Jianfeng Wang; Yunjie Li; Jian He; Jiyu Han; Hongyan Xu; Sen Liang; Nasi Ai (Food Bioscience, 2026)

Enhancement of nitrobenzene degradation by co-pyrolysis biochars in sulfide-mediated aqueous environment:adsorption and reduction contribution - Yadong Yang; Tao Wang; Kangshun Wang; Sen Zhang; Lingzhi He; Qiangshun Wu (Environmental Research, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

CRODNet: Cascaded learning network for contactless top-view cattle rotated object detection - Hui Kang; Yuqi Zhang; Longxiang Li; Chunyang Li; Sen Wang; Kai Niu; Yue Rong; Zhiqiang He (Computers and Electronics in Agriculture, 2026)

Small-strain stiffness of in situ granite residual soil: Experimental comparison under biased and isotropic consolidation - Song Yin; Ya He; Sen Li; Siyue Zheng; Xianwei Zhang; Xinming Li (Soil Dynamics and Earthquake Engineering, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

Cylindrical PVC pipe: 2D macro light trapper and macroscopic photoprotective tube for fabricating high-concentration brine desalinators? - Sen Ai; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Jun-Shuai Li; Xiang-Hu Gao (Desalination, 2026)

Latitudinal clines in life-history traits of the cabbage beetle, Colaphellus bowringi: showing a stepwise pattern - Li-Li Huang; Fang-Sen Xue; Jian-Jun Tang; Hai-Min He (Oecologia, 2026)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

Ecological and energy sector impacts of bisphenol compounds: A case study on their distribution in Bohai Bay seawater - Siao Zhang; Siyu Yi; Zeng Liu; Sen Wang; Xi He; Lifeng Shi; Yukuo Liu; Hao Wang (Regional Studies in Marine Science, 2025)

Phase-regulated colloidal FeS for controlled sulfidation and precise copper–arsenic separation under strongly acidic conditions - Xingfei Zhang; Wei Sun; Haisheng Han; Xianzhong Bu; Sen Wang; Xuewen Song; Chenglong Lu; Jiwei Xue; He Wan; Chonghui Zhang (Process Safety and Environmental Protection, 2025)

Lateral dynamic response of bucket foundation in clay considering installation effect - Yufan He; Wenbo Tu; M. Hesham El Naggar; Xiaoqiang Gu; Yaoyu Jia; Lixiang Wei; Sen Li (Ocean Engineering, 2025)

Effect of diapause duration on thermal tolerance in the cabbage beetle Colaphellus bowringi Baly - Yan Ni; Ying-Fang Li; Fang-Sen Xue; Li-Li Huang; Hai-Min He (Journal of Insect Physiology, 2025)

Strong carbonate buffering in karst cascade river-reservoir systems constrains CO2 production and emissions - Xuan Hu; Wanfa Wang; Lishan Ran; Sen Xu; Qiong Han; Francesco Ulloa-Cedamanos; Jun Zhong; Bei-Bei Chen; Shengde Yu; Dengming He; Wenhong Shi; Siqin Xu; et al. (Geochimica et Cosmochimica Acta, 2025)

Mechanism and Improvement of Electrocoagulation Technology for Removing Microplastics from Wastewater-Current Status and Future Directions - Siao Zhang; Sen Wang; Zeng Liu; Xi He; Lifeng Shi; Yukuo Liu; Hao Wang (Water, Air, & Soil Pollution, 2025)

Mechanism and Treatment Effect of Antibiotic Resistance Genes in Wastewater During Constructed Wetland Operation - Zeng Liu; Siao Zhang; Yanling Guan; Sen Wang; Xi He; Chunpeng Leng; Yunlong Zhou; Yue Yuan; Lin Liu; Fuping Li; Hao Wang (Water Conservation Science and Engineering, 2025)

Efficient directional biosynthesis of isoquercitrin from quercetin by Bacillus subtilis CD-2 and its anti-inflammatory activity - Ju Han; Jingru Ma; Ruiqi He; Fan Yang; Jingyi Meng; Jiaqi Liu; Fanxing Shi; Jinao Duan; Liangliang Chen; Sen Zhang (Natural Product Research, 2025)

Influence of pile-soil relative rigidity on cyclically loaded pile in undrained clay with varying load magnitudes - He Cui; Sen Li; Senjie Tong; Maosong Huang; Zhenhao Shi; Bin Wang (Ocean Engineering, 2025)

Synergistic dewatering of construction foundation sludge via tripartite strategy: High-efficiency flocculation and floc skeleton reinforcement mechanism - Shixin Zhang; Jiahui Zhang; Dilin He; Yixin Zhang; Shiyu Yuan; Xiaomin Tang; Huaili Zheng; Sen Li; Yuxin Chen; Yu Qin (Journal of Environmental Chemical Engineering, 2025)

Exploring the limit of Cu-based small-pore zeolite framework collapse during hydrothermal aging in NO abatement from diesel vehicle exhaust - Wenqing Ding; Yu Sun; Jinpeng Du; Zhongqi Liu; Jingjing Liu; Tongliang Zhang; Wenpo Shan; Xiaoyan Shi; Sen Xue; Xuewang Han; Yunbo Yu; Yulong Shan; et al. (Journal of Environmental Sciences, 2025)

The mobility of U(VI) associated with Fe(II)-induced transformation of schwertmannite and its reductive dissolution and re-precipitation in AMD environment - Chang He; Yu Ning; Yilian Li; Hongyan Guo; Zhe Yang; Sen Yang; Fengcheng Jiang (Applied Geochemistry, 2025)

Overexpression of AtBES1D in tomato enhances BR response and accelerates fruit ripening - Sen He; Xiubo Xia; Junhui Yang; Jinyang Xin; Siqi Chen; Chengguo Jia (Journal of Plant Physiology, 2025)

Modulating band structure of MoO3 via W-doped for enhanced photo-induced charge transfer and SERS detection - Hongwen Cao; Yunpeng Cao; Jia He; Xin Xie; Zhijun Wang; Sen Sun; Rui Zhong; Lei Sun; Yihan Wang; Kun Zhang (Chemical Engineering Journal, 2025)

Effects of Spartina alterniflora invasion on carbon fixation and sulfate reduction in a subtropical marine mangrove ecosystem - Shuming Mo; Xiaoling Wu; Muhammad Kashif; Sen Zeng; Yimeng Sang; Can Meng; Sheng He; Chengjian Jiang (Marine Pollution Bulletin, 2025)

The ecotoxicology of microplastics and nano-plastics research on Daphnia_Current status and future directions - Siao Zhang; Zeng Liu; Sen Wang; Xi He; Lifeng Shi; Yukuo Liu; Hao Wang (Journal of Environmental Chemical Engineering, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

Significant Impact of UV Exposure on Litter Decomposition Across Diverse Climate Zones - Sen Yang; Zhou Jia; Pengfei Chang; Yuntao Wu; Junsheng Huang; Jing Wang; Meifeng Deng; Jiao Su; Songbai Hong; Yue He; Juntao Zhu; Pujin Zhang; et al. (Global Change Biology, 2025)
Litter decomposition is a critical biogeochemical process for carbon and nutrient cycling in terrestrial ecosystems. Ultraviolet (UV) radiation has been recognized to accelerate litter‐derived C release in arid and semi‐arid ecosystems; yet its spatial controls on determining the regional pattern of litter decomposition are poorly explored. Moreover, the limited understanding of how UV radiation interacts with traditional decomposition drivers, such as climate and litter quality, significantly restricts our ability to accurately quantify the contribution of UV‐driven photodegradation to large‐scale carbon turnover. In this study, we established a coordinated, distributed UV‐manipulation network, spanning 3500‐km and covering four grassland ecosystem types, to assess the impact of UV radiation on litter decomposition across gradients of aridity, UV dose, and litter lignin/N ratio. With a modified modeling approach, we further quantified the contribution of UV radiation to litter layer decomposition across temperate grasslands in China. After more than three years in the field, we found that UV attenuation reduced litter mass loss across climatic gradients. The UV‐induced facilitation effect primarily occurs in the latter stages of decomposition. The strength of photochemical degradation increased with higher cumulative UV dose, amplified by environmental aridity and litter lignin/N ratio. Across Chinese temperate grasslands, UV exposure shortens mean residence time (MRT) of litter layer by 0.40 years, representing a 16.85% reduction. Hotspots, where UV reduces MRT by over a year, are primarily located in arid and high‐altitude grasslands. The sensitivity analysis indicates that the vulnerability of grassland litter decomposition to UV fluctuations intensifies as environmental aridity increases. These findings reveal the pervasiveness of UV‐driven litter photodegradation across diverse grasslands and provide a comprehensive framework to improve the predictability of litter‐originated C turnover in dryland ecosystems, enabling more constrained projections of terrestrial carbon‐climate feedbacks in the context of global UV fluctuations and aridification.

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

The pressure field inside water-rich cracks of tunnel linings during high-speed train passing through tunnels using air–water two-phase flow simulation - Hong He; Wei-Chao Yang; Yi-Kang Liu; Lun Zhao; E Deng; Lu-Sen Luo (Tunnelling and Underground Space Technology, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Untargeted metabolomics and network pharmacology reveal the uric acid-lowering effects of alcohol extract of Gnaphalium affine and its extracts in hyperuricemic rats - Chen Wang; Xinchao He; Lijuan Rao; Jiajing Liao; Jin Qian; Xuefeng Yu; Sen Mei; Suqin Lin; Linqian Xu; Guiming Fu; Yin Wan (Food Bioscience, 2025)

Salt pollution acts as a photothermal material in an SSAC-based inverted bilayered desalinating evaporator assembled with a light trapper - Sen Ai; Yi-Nuo Wang; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Jun-Shuai Li; Xiang-Hu Gao (Journal of Water Process Engineering, 2025)

The transformation from a macroscopic 1D light trapper to a 3D light trapper and the siphoning effect on the desalinating evaporator - Sen Ai; Yi-Nuo Wang; Jun-Shuai Li; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Xiang-Hu Gao (Desalination, 2025)

Structural characterizations and antiaging activities of hydrolyzed low-molecular-weight polysaccharides from Polygoni Multiflori Radix Praeparata - Wei Xu; Xue-Jian Li; Yu-Sen Zhong; Jia-Qi He; Wei Xie; You-Kun Kang; Hua-Zhong Ying; Chen-Huan Yu (Carbohydrate Polymers, 2025)

The capsid protein p72 specific mAb and the corresponding novel epitope based ELISAs for detection of ASFV infection - Jiajia Zhang; Ziyan Sun; Shaohua Sun; Kaili Zhang; Dafu Deng; Ping He; Pingping Zhang; Nengwen Xia; Sen Jiang; Wanglong Zheng; Francois Meurens; Jianzhong Zhu (Veterinary Microbiology, 2025)

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Thin basaltic regolith at the Chang'e-6 landing site - Sheng Gou; Zongyu Yue; Yangting Lin; Kaichang Di; Patrick C. Pinet; Wei Yang; Yuyang He; Yi Chen; Roberto Bugiolacchi; Hengci Tian; Honglei Lin; Sen Hu (Earth and Planetary Science Letters, 2025)

Symmetric responses of microbial carbon and nutrient limitations to warming and cooling in boreal forests: Insights from a transplant experiment - Sen Lu; Dongdong Zhang; Shuanglin Zhao; Ziqiao Yang; Ying Zhang; Lili Yang; Gongxiu He; Li Ji (Applied Soil Ecology, 2025)

A nucleocapsid monoclonal antibody based sandwich ELISA for the general detection of both PRRSV-2 and PRRSV-1 - Shaohua Sun; Kaili Zhang; Jiajia Zhang; Ping He; Pingping Zhang; Dafu Deng; Chenglin Chi; Sen Jiang; Wanglong Zheng; Nanhua Chen; Jianzhong Zhu (Veterinary Microbiology, 2025)

Microbial-mediated carbon metabolism in the subtropical marine mangroves affected by shrimp pond discharge - Sen Zeng; Shuming Mo; Xiaoling Wu; Can Meng; Pai Peng; Muhammad Kashif; Jinhui Li; Sheng He; Chengjian Jiang (Marine Environmental Research, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Quantitative reconstruction of soil erosion process in a crater lake catchment during the Holocene, Southwest China - Hongfei Zhao; Zhuoya Zhang; Xin Zhou; Hongming He; Sen Wang; Shiwei Jiang; Xiaoyan Liu; Xuanqiao Liu; Anze Chen; Yong Luo; Wangyang Kan (CATENA, 2025)

Treg Upregulation by Treadmill Training Accelerates Myelin Repair Post-Ischemia - Juan Zhong; Tao Liu; Yingxi He; Ying Zhu; Sen Li; Yuan Liu; Ce Yang; Lehua Yu; Lu Pan; Ying Yin; Botao Tan (Journal of Neuroimmune Pharmacology, 2025)

De novo biosynthesis of dihydroquercetin in an engineered Yarrowia lipolytica with enhanced (2S)-eriodictyol - Qian He; Mingyu Yue; Mengsu Liu; Xuefeng Ren; Huijing Wang; Jianbin Chen; Jinbo Xiang; Wenjing He; Sen Ye; Song Gao; Sha Xu; Yijian Rao; et al. (Food Bioscience, 2025)

Atmosphere-dependent pyrolytic transformability of glass fiber/epoxy resin composites in waste wind turbine blades - Siqi Chen; Jingyong Liu; Ziting Lin; Sen Lin; Liangzhong Li; Yan Chen; Fatih Evrendilek; Weixin Li; Wenxiao Huang; Chenyu Yang; Haoran Yuan; Yao He; et al. (Chemical Engineering Journal, 2025)

Constructing mullite-based catalyst by surface oxygen vacancy regulation for propane oxidation at reduced temperature - Sen Fu; Yao Nian; Changqing He; Cong Zhang; Lin He; Yong Wang; Shinee Lou; Hong Sui (Chemical Engineering Journal, 2025)

Data assimilation of turbulent flow in a large-scale steam generator: Part I- Iterative ensemble-Kalman filter-based reconstruction - Sen Li; Yuheng Lu; Chuangxin He; Chunjing Song; Yingzheng Liu; Yun Zhong (Annals of Nuclear Energy, 2025)

The role of copper ions in improving the flotation of chalcopyrite at low temperatures - Chonghui Zhang; Yihan Su; Tingshu He; Xianzhong Bu; He Wan; Sen Wang; Jiwei Xue (Minerals Engineering, 2025)

Hydrographic restriction conditions in the Middle and Upper Yangtze region during the Early Silurian post-glacial transgression: Constraints from major, trace elemental geochemistry and Mo-TOC relationship - Chuan Wang; Tian Dong; Zhiliang He; Xiaowen Guo; Sen Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Corrigendum to “Revisiting the formation of lunar anorthosites via the Rb-Sr isotope systematics” [Lithos, volume 486–487, (2024) 107780] - Qing Zhou; Heng-Ci Tian; Liyu Shan; Sen Hu; Wei Yang; Maoyong He; Lei Zhang; Yangting Lin; Xianhua Li (Lithos, 2024)

Fe2O3, Al2O3, or sludge ash-catalyzed pyrolysis of typical 3D printing waste toward tackling plastic pollution - Ziting Lin; Jingyong Liu; Liangzhong Li; Haiming Cai; Sen Lin; Fatih Evrendilek; Siqi Chen; Xin Chen; Tao Chen; Yao He (Journal of Hazardous Materials, 2024)

Complex basalt evolution in the Chang'e-6 landing area - Sheng Gou; Zongyu Yue; Yangting Lin; Kaichang Di; Patrick C. Pinet; Roberto Bugiolacchi; Yuyang He; Wei Yang; Honglei Lin; Hengci Tian; Sen Hu (Earth and Planetary Science Letters, 2024)

Multiple hydrothermal events at martian surface revealed by H and Cl isotope systematics of melt inclusions and hydrous minerals from chassignite NWA 2737 - Sen Hu; Mahesh Anand; Ian A. Franchi; Xuchao Zhao; Alice Stephant; Magali Bonifacie; Huicun He; Wei Yang; Jialong Hao; Yangting Lin (Earth and Planetary Science Letters, 2024)

Distribution, assessment, and causality analysis of soil heavy metals pollution in complex contaminated sites: a case study of a chemical plant - Fengcheng Jiang; Luyao Wang; Zhi Tang; Sen Yang; Mingshi Wang; Xixi Feng; Chang He; Qiao Han; Fayang Guo; Baoguo Yang (Environmental Geochemistry and Health, 2024)

Synthesis of Fe-ZSM-5 zeolite from high iron-containing palygorskite with peroxidase-like catalytic performance - Fengya Ran; Meng He; Shiyong Sun; Rui Lv; Sen Lin; Ke Wang; Yevgeny Aleksandrovich Golubev; Olga Borisovna Kotova; Elena Leonidovna Kotova (Applied Clay Science, 2024)

Revisiting the formation of lunar anorthosites via the Rb Sr isotope systematics - Qing Zhou; Heng-Ci Tian; Liyu Shan; Sen Hu; Wei Yang; Maoyong He; Lei Zhang; Yangting Lin; Xianhua Li (Lithos, 2024)

Selective removal of chromium and chloride by flow electrode capacitive deionization (FCDI) with carrier-facilitated ion exchange membrane - Ming Tan; Sen Yang; Chunling Song; Zixuan He; Jixue Wang; Yang Liu; Fei Liu; Yang Zhang (Chemical Engineering Journal, 2024)

Advanced hydrogels for pancreatic fistula prevention, management and treatment: requirements, advances, and prospects - Yajuan He; Shihong Shen; Sen Zhang; Pan Wang; Dan Zeng; Xiaoxuan Ma; Daidi Fan (Chemical Engineering Journal, 2024)

Versatile and efficient mammalian genome editing with Type I-C CRISPR System of Desulfovibrio vulgaris - Pan Li; Dingcai Dong; Fei Gao; Yuyang Xie; Honglin Huang; Siwei Sun; Zhao Ma; Cheng He; Jinsheng Lai; Xuguang Du; Sen Wu (Science China Life Sciences, 2024)

Spontaneous imbibition of unsaturated sandstone under different vertical temperature gradients: neutron radiography experiments and dynamic models - Jinbao Guo; Yixin Zhao; Linfeng He; Xiaodong Guo; Hua Shen; Sen Gao (Advances in Water Resources, 2024)

Aflatoxin B1 as a complicit in intestinal damage caused by Eimeria ovinoidalis in lambs: Novel insights to reveal parasite-gut battle - Pan Chen; Wen-li Ding; Bo-wen Xu; Mujeeb Ur Rehman; Kai-li Liu; Yan-feng He; Sen-yang Li; Fu-chun Jian; Shu-cheng(淑成) Huang(黄) (Science of The Total Environment, 2024)

Entire co-combustion lifecycle of sewage sludge and water lettuce (Pistia stratiotes L.) and its controls over energetic and environmental benefits - Jiayu Liang; Jingyong Liu; Fatih Evrendilek; Zhibin Chen; Liangzhong Li; Sen Lin; Ziting Lin; Lei Li; Xieyuan Wu; Li Wang; Yao He (Chemical Engineering Journal, 2024)

Identification of 3-hydroxyaspartate with two chiral centers by capillary electrophoresis-mass spectrometry and vibrational circular dichroism independent of single enantiomer standard - Sen Yang; Li Wu; Yujian He; Xiangjun Li (Analytica Chimica Acta, 2024)

Co-pyrolytic drivers and volatiles of 3D printing waste and textile dyeing sludge and their multi-objective optimization - Ziting Lin; Xiaoming Li; Jingfang Mou; Fatih Evrendilek; Jingyong Liu; Jiayu Liang; Sen Lin; Haiming Cai; Yao He; Guanzheng Zhuang; Chunxiao Yang (Chemical Engineering Journal, 2024)

Self-cleaning and multi-active sites amphoteric composite sponges: Efficient removal, selective adsorption and photocatalyst substrates of dyes - Qiang Yang; Jing Guo; Qiang Yao; Sen Zhang; Shi Feng; Fucheng Guan; Zheng Li; Xin Zhang; Yi Xu; Jiahao He (Chemical Engineering Journal, 2024)

Multi-strategy synergistic scheme for progressive construction and optimization of non-covalent all-polysaccharide double-network hydrogels - Qiang Yang; Jing Guo; Sen Zhang; Shi Feng; Qiang Yao; Da Bao; Yi Xu; Fucheng Guan; Xin Zhang; Jiahao He (Chemical Engineering Journal, 2024)

Return to the Moon: New perspectives on lunar exploration - Yangting Lin; Wei Yang; Hui Zhang; Hejiu Hui; Sen Hu; Long Xiao; Jianzhong Liu; Zhiyong Xiao; Zongyu Yue; Jinhai Zhang; Yang Liu; Jing Yang; et al. (Science Bulletin, 2024)

Physicochemical, thermodynamic, and kinetic controls on volatile products, bio-oils, and biochars of Lycium barbarum pyrolysis and their multi-objective optimization - Siqi Chen; Sen Lin; Shengzheng Huang; Bin Cai; Jiayu Liang; Zhibin Chen; Fatih Evrendilek; Yao He; Sheng Zhong; Zuoyi Yang; Chunxiao Yang; Jingyong Liu (Fuel, 2024)

Micro-helical Ni3Fe chain encapsulated in ultralight MXene/C aerogel to realize multi-functionality: Radar stealth, thermal insulation, fire resistance, and mechanical properties - Sen Lin; Jing Lin; Zhiqiang Xiong; Xue He; Xin Li; Chongbo Liu; Chengying Wang; Xiaojun Zeng; Xuliang Nie; Renchao Che (Chemical Engineering Journal, 2024)

Atmosphere-dependent combustion of Ganoderma lucidum biomass toward its enhanced transformability into green energy - Hanlin Cao; Hongda Zhan; Jianying Qi; Sen Lin; Mingzhong Ren; Jiayu Liang; Fatih Evrendilek; Yao He; Jingyong Liu (Environmental Science and Pollution Research, 2024)

Mechanism of the denitrification of secondary aluminum dross (SAD) during water leaching with delayed addition of a low dosage of sodium hydroxide - Chuan Wang; Yongchun Guo; YongYi He; Sen Li; Jun Liu; Hu Liu (Hydrometallurgy, 2024)

Multiplicative effects of co-incineration of sewage sludge and wasted oyster shells in air, CO2, and steam atmospheres on P speciation and bioavailability and metal ecotoxicity - Jiayu Liang; Zhiwei Huang; Jingyong Liu; Sen Lin; Ziting Lin; Fatih Evrendilek; Wuming Xie; Guanzheng Zhuang; Yao He; Li Wang; Chunxiao Yang (Chemical Engineering Journal, 2024)

Dynamic traffic safety risk assessment in road tunnel entrance zone based on drivers' psychophysiological perception states: Methodology and case-study insights - Jia'an Niu; Bo Liang; Yiik Diew Wong; Shiyong He; Can Qin; Sen Wen (Tunnelling and Underground Space Technology, 2024)

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Black kitchen waste based solar evaporator employing radiative cooling film as difffuse substrate for efficient desalination - Sen Ai; Yi-Nuo Wang; Tong-Jun Li; Yong-Zhi Chen; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Xiang-Hu Gao (Desalination, 2024)

Analysis of Fracture Evolution Characteristics and Formation Mechanism of Inter-Layer Rock Under Different Mining Areas - Jie Zhang; Jianjun Wu; Tao Yang; Sen Yang; Yifeng He; Shoushi Gao; Bing Peng (Rock Mechanics and Rock Engineering, 2024)

Effects of displacement rate on mechanical behaviors and failure mechanism of non-caking coal in Brazilian splitting tests - Bin Liu; Yixin Zhao; Sen Gao; Hongwei Zhang; Teng Teng; Xiang He (Bulletin of Engineering Geology and the Environment, 2024)

The impact of silica diagenesis on shale rock mechanical properties: An example from the upper ordovician-lower silurian wufeng-longmaxi formations, Southeast Sichuan Basin, South China - Sen Liu; Tian Dong; Dongfeng Hu; Qing He (Marine and Petroleum Geology, 2024)

Catalytic co-pyrolysis of coffee grounds and polyethylene: A comparison of HZSM-5 and HY - Jiawei Fu; Sen Lin; Bin Cai; Jiayu Liang; Zhibin Chen; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Chunxiao Yang; Yao He; Shuiyu Sun; Jingyong Liu (Fuel, 2024)

Photosynthetic live microorganism-incorporated hydrogels promote diabetic wound healing via self-powering and oxygen production - Yan Wu; Meiyun Li; Ruiying He; Lan Xiao; Sen Liu; Kaiyuan Chen; Huifen Qiang; Keqin Ji; Luxin Li; Yongkui Yin; Xiaohuan Yuan; Meng Li; et al. (Chemical Engineering Journal, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

Mechanism of propylene effect on the NH3-SCR performance of Cu-SSZ-13 catalyst - Wenqing Ding; Yu Sun; Jingjing Liu; Sen Xue; Xuewang Han; Zidi Yan; Yunbo Yu; Yulong Shan; Hong He (Chemical Engineering Journal, 2024)

Corrigendum to “Kidney injury contributes to edema of zebrafish larvae caused by quantum dots” [Sci. Total Environ. 908 (2024) 168420] - Luanjin Wang; Cixin Liang; Naying Zheng; Chunyan Yang; Sen Yan; Xiang Wang; Zhenghong Zuo; Chengyong He (Science of The Total Environment, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Moisture-Assisted Molecular Sieve-Confined Synthesis of Lead-Free CsAgCl2 Perovskite-Derivative Nanocrystals - Sen Li; Yixing Zhao; Liqiong Du; Yongyi He; Ruyi Wang; Yongchun Guo; Chuan Wang; Tingfang Tian; Li Wang; Hu Liu (Chemical Engineering Journal, 2024)

Rational design of crystalline/amorphous nickel manganese phosphate octahydrate heterostructure for high-performance aqueous and all-solid-state asymmetric supercapacitors - Min Li; Min Li; Mingshu Zhao; Bing Wu; Stefanos Mourdikoudis; Shuangying Wei; Filipa M. Oliveira; Junjie He; Lukáš Děkanovský; Jan Luxa; Sen Yang; Zdeněk Sofer (Chemical Engineering Journal, 2024)

Activated carbon-boosted BiOI in CO2 adsorption and electron transfer for photothermally catalyzed CO2 oxidative dehydrogenation of propane - Run-Qing Miao; Zhen-Hong He; Bao-Ting Wu; Jiajie Liu; Sen-Wang Wang; Kuan Wang; Weitao Wang; Lu Li; Zhao-Tie Liu (Chemical Engineering Journal, 2024)

Kidney injury contributes to edema of zebrafish larvae caused by quantum dots - Luanjin Wang; Cixin Liang; Naying Zheng; Chunyan Yang; Sen Yan; Xiang Wang; Zhenghong Zuo; Chengyong He (Science of The Total Environment, 2024)

RsCDF3, a member of Cycling Dof Factors, positively regulates cold tolerance via auto-regulation and repressing two RsRbohs transcription in radish (Raphanus sativus L.) - Min He; Xiaoli Zhang; Yingfei Ma; Xinyu Zhang; Sen Chen; Yuelin Zhu; Yan Wang; Liwang Liu; Yinbo Ma; Lun Wang; Liang Xu (Plant Science, 2023)

The organism fate of inland freshwater system under micro-/nano-plastic pollution: A review of past decade - Ji Liang; Sen Xiong; Chunlin He; Zhaobin Song; Song Yang; Daiqiang Ma; Wenchu Yan; Hong Wang; Rabia Tahir; Mingming Han (Aquatic Toxicology, 2023)

Comprehensive treatments of aluminum dross in China: A critical review - Chuan Wang; Sen Li; Yongchun Guo; YongYi He; Jun Liu; Hu Liu (Journal of Environmental Management, 2023)

Formation of natural fractures and their impact on shale oil accumulation in the Mahu Sag, Junggar Basin, NW China - Xiaoyu Du; Zhijun Jin; Lianbo Zeng; Guoping Liu; Wenjun He; Mehdi Ostadhassan; Yong Song; Xinping Liang; Sen Yang; Guoqing Lu (International Journal of Coal Geology, 2023)

Characteristics and controlling factors of natural fractures in deep lacustrine shale oil reservoirs of the Permian Fengcheng Formation in the Mahu Sag, Junggar Basin, China - Xiaoyu Du; Zhijun Jin; Lianbo Zeng; Guoping Liu; Wenjun He; Mehdi Ostadhassan; XinPing Liang; Sen Yang; Guoqing Lu (Journal of Structural Geology, 2023)

Molecular insight into DOM fate using EEM-PARAFAC and FT-ICR MS and concomitant heavy metal behaviors in biologically treated landfill leachate during coagulation: Al speciation dependence - Libing Liu; Lei Du; Sen Lu; Bo Yang; Xu Zhao; Deli Wu; Xunchang Fei; Hongping He; Dongsheng Wang (Journal of Hazardous Materials, 2023)

Phase-transitioned lysozyme-mediated fabrication of zeolitic imidazole framework-8 hybrid membrane with enhanced separation and antifouling properties - Sen Zeng; Qingqing He; Qianting Wang; Junhui Si; Zhixiang Cui (Journal of Environmental Chemical Engineering, 2023)

A dye-based desalinating evaporator independent on solar absorber of excellent optical properties for efficient desalination - Sen Ai; Yi-Nuo Wang; Tong-Jun Li; Yong-Zhi Chen; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Xiang-Hu Gao (Desalination, 2023)

Which molecular marker is better? Comparative analyses of COI and ITS2 in molecular identification of Trichogramma (Hymenoptera: Trichogrammatidae) - Ao-Kai Wang; Fang-Yi Li; De-Sen Wang; Yu-Rong He; Yuan-Xi Li; Zhi-Chao Yan (BioControl, 2023)

DNA origami-mediated plasmonic dimer nanoantenna-based SERS biosensor for ultrasensitive determination of trace diethylstilbestrol - Sen Li; Baodi Shi; Defu He; Huanying Zhou; Zhixian Gao (Journal of Hazardous Materials, 2023)

Variation of arbuscular mycorrhizal fungi communities in the rhizosphere soil of Eucalyptus plantations based on different stand ages and its effect on phosphorus fractionation - Shengyuan Liu; Xiangyun Lu; Gaoming Yang; Chun He; Yutian Shi; Chenji Li; Sen Liu; Ye Wang; Zixuan Wang; Lijun Chen; Tao Liu; Lichao Wu (Applied Soil Ecology, 2023)

Sun-pointing safe control for atmospheric environment monitoring satellite using magnetic actuation - Yikang He; Zhenhua Wang; Sen Yang; Wen He (Advances in Space Research, 2023)

Nitrogen rather than carbon released by litter decomposition mediates nutrient relationships in a multispecies forest plantation with hemiparasite - Fangcuo Qin; Junkun Lu; Zhenshuang Li; Sen Meng; Shengkun Wang; Junfeng Liang; Xinhua He (Science of The Total Environment, 2023)

Graphene nano zinc oxide reduces the expression and release of antibiotic resistance-related genes and virulence factors in animal manure - Haibo Zhang; Weikun Guan; Jun Shu; Sen Yu; Yingmin Xiong; Gao Liu; Yuhong Zhong; Jia Chen; Zhigang Zhao; Ning He; Qingfeng Xing; Dongsheng Guo; et al. (Science of The Total Environment, 2023)

A self-intensified inverted evaporation model constructed by high entropy spectrally selective absorber coating (SSAC) for brine water concentration - Sen Ai; Yi-Nuo Wang; Tong-Jun Li; Yong-Zhi Chen; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Xiang-Hu Gao (Journal of Water Process Engineering, 2023)

Life history responses of the small brown planthopper Laodelphax striatellus to temperature change - Lan Xiao; Li-Li Huang; Hai-Min He; Fang-Sen Xue; Jian-Jun Tang (Journal of Thermal Biology, 2023)

Tomato recognition and location algorithm based on improved YOLOv5 - Tianhua Li; Meng Sun; Qinghai He; Guanshan Zhang; Guoying Shi; Xiaoming Ding; Sen Lin (Computers and Electronics in Agriculture, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Two new chemical constituents from the leaves of Illicium dunnianum - Jun-Ran Shao; Sen-Ju Ma; Ting Li; Xiao-Qing He; Zhen-Zhong Wang; Wei Xiao; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2023)

Nano-sized alumina supported palladium catalysts for methane combustion with excellent thermal stability - Wei Shi; Guangyan Xu; Xuewang Han; Yingjie Wang; Zhi Liu; Sen Xue; Nannan Sun; Xiaoyan Shi; Yunbo Yu; Hong He (Journal of Environmental Sciences, 2023)

Magnetic hydrogel-based flexible actuators: A comprehensive review on design, properties, and applications - Yuan He; Jie Tang; Yang Hu; Sen Yang; Feng Xu; Miklos Zrínyi; Yong Mei Chen (Chemical Engineering Journal, 2023)

A high-strength, environmentally stable, and recyclable starch/PVA organohydrogel electrolyte for flexible all-solid-state supercapacitor - Li He; Jinquan Wang; Sen Weng; Xiancai Jiang (Carbohydrate Polymers, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Fabrication of outstanding mechanical performance engineered poly (lactic acid)/thermoplastic poly(ester)urethane in-situ nanofiber composites with a large-scale industrial innovation methodology - Yue He; Cong Fang; Wen-Hua Xu; Ling-Cao Tan; Sen Qin; Xiao-Chun Yin; Yan-Hong Feng; Chul B. Park; Jin-Ping Qu (Chemical Engineering Journal, 2023)

Pollution characteristics of full-scale butterfly valves: Risk assessment of heavy metal release behavior influenced by the bacterial communities and corrosion products - Shichao Jia; Yimei Tian; Bo Zheng; Yarong Song; Nan He; Zhu Peng; Sen Peng; Weigao Zhao (Bioresource Technology Reports, 2023)

Effect of soil moisture on the multi-component decomposition of wetland macrophytes - Song Xu; Guojian He; Hongwei Fang; Siwen Liu; Sen Bai (Hydrobiologia, 2023)

Study on sex-linked region and sex determination candidate gene using a high-quality genome assembly in yellow drum - Sha Sun; Chaowei Song; Fang Han; Qiwei He; Jieping Liu; Sen Zhang; Wei Han; Kun Ye; Zhaofang Han; Zhiyong Wang; Wanbo Li (Aquaculture, 2023)

Experimental study on consolidation and strength properties of tailings with different particle size distribution characteristics - Sen Tian; Yi He; Ruyi Bai; Jie Chen; Guangjin Wang (Natural Hazards, 2022)

Effects of montmorillonite on the adsorption of Fe(II) by ferrihydrite and its phase transformation at different pH - Chang He; Zhe Yang; Yu Ning; Sen Yang; Fengcheng Jiang; Jiayi Zhang (Environmental Science and Pollution Research, 2022)

Deciphering the Heterogeneity of Mitochondrial Functions During Hematopoietic Lineage Differentiation - Haoyue Liang; Shuxu Dong; Weichao Fu; Sen Zhang; Wenying Yu; Fang Dong; Baolin He; Jinhong Wang; Yingdai Gao; Yuan Zhou; Yongxin Ru (Stem Cell Reviews and Reports, 2022)

A CNN Model for Cardiac Arrhythmias Classification Based on Individual ECG Signals - Yuan Zhang; Sen Liu; Zhihui He; Yuwei Zhang; Changming Wang (Cardiovascular Engineering and Technology, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

IDDLncLoc: Subcellular Localization of LncRNAs Based on a Framework for Imbalanced Data Distributions - Yan Wang; Xiaopeng Zhu; Lili Yang; Xuemei Hu; Kai He; Cuinan Yu; Shaoqing Jiao; Jiali Chen; Rui Guo; Sen Yang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

A Shuttling Protein Kank1 Plays Important Role in the Sex Determination in Yellow Drum - Sha Sun; Jieping Liu; Sen Zhang; Qiwei He; Wei Han; Kun Ye; Fang Han; Wanbo Li; Zhiyong Wang (Frontiers in Marine Science, 2022)
Sex is one of the most important scientific topics, and the existence of sex dimorphism is a conserved feature in vertebrate taxa. The research on sex-determining genes and sex chromosome evolution is a hot topic in biology. The majority of sex-determining genes expressed in somatic cells, and reciprocal interactions between germ cells and somatic cells, are important for gonadal differentiation. However, the knowledge of how signals are transmitted between somatic cells and germ cells remains unclear. In this study, we confirmed the 36 dph was a sex determination critical stage in yellow drum through transcriptome analysis at the early development stages. We further found that Kank1 participated in the germ cells’ motility process in yellow drum through KEGG pathway analysis together with protein-protein interaction network. With the dual-luciferase reporter assay, we detected that Kank1 increased the transcription of dmrt1_Luc gene in CHO cells and 293T cells. Additionally, we observed that Kank1 was not only expressed in the cytoplasm but also in the nucleus in CHO cells through a fluorescence microscope. These results suggest that Kank1 acts as a shuttling protein as in humans and may play a difunctional role at the early gonad development stage in yellow drum, and it not only participated in the germ cells’ motility but also increased the expression of dmrt1 in yellow drum.

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Effects of organic acids on the chemotaxis profiles and biocontrol traits of antagonistic bacterial endophytes against root-rot disease in Panax notoginseng - Li Ma; Wu-Qin Wang; Rui Shi; Xue-Mei Zhang; Xin Li; Yu-Sen Yang; Ming He Mo (Antonie van Leeuwenhoek, 2021)

Model test on support scheme for carbonaceous slate tunnel in high geostress zone at high depth - Zhi-gang Tao; Shu-lin Ren; Gan Li; Hao-tian Xu; Sen-lin Luo; Man-chao He (Journal of Mountain Science, 2021)

Effect of polymer on strength and permeability of marine clay - Hai-lei Kou; He Jia; Jian Chu; Pei-gang Zheng; A-sen Liu (Marine Georesources & Geotechnology, 2021)

The Effects of Different Fluorescent Indicators in Observing the Changes of the Mitochondrial Membrane Potential during Oxidative Stress-Induced Mitochondrial Injury of Cardiac H9c2 Cells - Yahan Sun; Kunyan Zhou; Mali He; Ying Gao; Danjie Zhang; Yanwen Bai; Yuezhao Lai; Mengying Liu; Xuechao Han; Sen Xu; Wei Tian; Jingman Xu (Journal of Fluorescence, 2020)

Expression and regulation of Smad2 by gonadotropins in the protogynous hermaphroditic ricefield eel (Monopterus albus) - Zhi He; Faqiang Deng; Sen Xiong; Yueping Cai; Zhide He; Xiongyan Wang; Song Li; Deying Yang; Taiming Yan (Fish Physiology and Biochemistry, 2020)

Lasiodiplodia spp. associated with Aquilaria crassna in Laos - Yu Wang; Sen Lin; Lin Zhao; Xiang Sun; Wei He; Ying Zhang; Yu-Cheng Dai (Mycological Progress, 2019)

Application of High-Throughput Sequencing to Evaluate the Genetic Diversity Among Wild Apple Species Indigenous to Shandong, China, and Introduced Cultivars - Yuansheng Chang; Ping He; Haibo Wang; Huifeng Li; Sen Wang; Linguang Li (Plant Molecular Biology Reporter, 2019)

Qualitative and quantitative analysis of chemical constituents of Ptychopetalum olacoides Benth - Xiao Tian; Sen Guo; Kan He; Marc Roller; Meiqi Yang; Qingchao Liu; Li Zhang; Chi-Tang Ho; Naisheng Bai (Natural Product Research, 2018)

Long-Term Selenium-Deficient Diet Induces Liver Damage by Altering Hepatocyte Ultrastructure and MMP1/3 and TIMP1/3 Expression in Growing Rats - Jing Han; Hua Liang; Jianhua Yi; Wuhong Tan; Shulan He; Sen Wang; Feng Li; Xiaofang Wu; Jing Ma; Xiaowei Shi; Xiong Guo; Chuanyi Bai (Biological Trace Element Research, 2017)

Soil nitrate–N residue, loss and accumulation affected by soil surface management and precipitation in a winter wheat-summer fallow system on dryland - Gang He; Zhaohui Wang; Fucui Li; Jian Dai; Xiaolong Ma; Qiang Li; Cheng Xue; Hanbing Cao; Sen Wang; Hui Liu; Laichao Luo; Ming Huang; et al. (Nutrient Cycling in Agroecosystems, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Ecological status classification of the Taizi River Basin, China: a comparison of integrated risk assessment approaches - Juntao Fan; Elena Semenzin; Wei Meng; Elisa Giubilato; Yuan Zhang; Andrea Critto; Alex Zabeo; Yun Zhou; Sen Ding; Jun Wan; Mengchang He; Chunye Lin (Environmental Science and Pollution Research, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Molecular cloning and characterization of gonadotropin subunits (GTHα, FSHβ and LHβ) and their regulation by hCG and GnRHa in Japanese sea bass (Lateolabrax japonicas) in vivo - Mei L. Chi; Meng Ni; Ji F. Li; Feng He; Kun Qian; Pei Zhang; Sen H. Chai; Hai S. Wen (Fish Physiology and Biochemistry, 2015)

Classification and identification of metal-accumulating plant species by cluster analysis - Wenhao Yang; He Li; Taoxiang Zhang; Lin Sen; Wuzhong Ni (Environmental Science and Pollution Research, 2014)

Identification of QTLs for seedling vigor in winter wheat - Xing-Mao Li; Xin-Min Chen; Yong-Gui Xiao; Xian-Chun Xia; De-Sen Wang; Zhong-Hu He; Hua-Jun Wang (Euphytica, 2014)

The association between a single nucleotide polymorphism rs11966200 in MHC region and clinical features of generalized vitiligo in Chinese Han population - Jin Tang; Jian Lan Liu; Cheng Zhang; Da Yan Hu; Su Min He; Xian Bo Zuo; Pei Guang Wang; Liang Dan Sun; Xue Jun Zhang; Sen Yang (Molecular Biology Reports, 2013)

Oxidative decarboxylation of mandelic acid derivative by recombinant Escherichia coli: a novel method of ethyl vanillin synthesis - Xiao-xia Pan; Jing-jing Li; Mei-gui Wang; Wen-sen He; Cheng-sheng Jia; Xiao-ming Zhang; Biao Feng; Da-li Li; Zeng Zeng (Biotechnology Letters, 2013)

Molecular characterization of a stress-response bZIP transcription factor in banana - Sen He; Wei Shan; Jian-fei Kuang; Hui Xie; Yun-yi Xiao; Wang-jin Lu; Jian-ye Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Characteristics and source of black carbon aerosols at Akedala station, Central Asia - Huiqin Wang; Qing He; Tao Liu; Feng Chen; Xinchun Liu; Yuting Zhong; Sen Yang (Meteorology and Atmospheric Physics, 2012)

Erratum to: Male Age Affects Female Mate Preference and Reproductive Performance in the Cabbage Beetle, Colaphellus bowringi - Xing-Ping Liu; Jing Xu; Hai-Min He; Xian-Ju Kuang; Fang-Sen Xue (Journal of Insect Behavior, 2011)

Male Age Affects Female Mate Preference and Reproductive Performance in the Cabbage Beetle, Colaphellus bowringi - Xing-Ping Liu; Jing Xu; Hai-Min He; Xian-Ju Kuang; Fang-Sen Xue (Journal of Insect Behavior, 2011)

Th17 promotes acute rejection following liver transplantation in rats - Xiao-jun Xie; Yu-fu Ye; Lin Zhou; Hai-yang Xie; Guo-ping Jiang; Xiao-wen Feng; Yong He; Qin-fen Xie; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Brap2 facilitates HsCdc14A Lys-63 linked ubiquitin modification - Jing-Sen Chen; Hai-Ying Hu; Shuo Zhang; Min He; Ren-Ming Hu (Biotechnology Letters, 2009)

Using SSR markers to determine the population genetic structure of wild apricot (Prunus armeniaca L.) in the Ily Valley of West China - He Tian-Ming; Chen Xue-Sen; Xu Zheng; Gao Jiang-Sheng; Lin Pei-Jun; Liu Wen; Liang Qing; Wu Yan (Genetic Resources and Crop Evolution, 2007)

Safety and whole-body antioxidant potential of a novel anthocyanin-rich formulation of edible berries - Debasis Bagchi; Sashwati Roy; Viren Patel; Guanglong He; Savita Khanna; Navdeep Ojha; Christina Phillips; Sumona Ghosh; Manashi Bagchi; Chandan K. Sen (Molecular and Cellular Biochemistry, 2006)

A study on cellular automata based on relational databases and spatio-temporal simulations of culture diffusion - Ping Luo; Qing-yun Du; Su-fang He; Sen Li; Gallagher Michael; Hui-en Niu (Chinese Geographical Science, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)